IL-36 Receptor Antagonist with Special Emphasis on IL-38. (January 2013) - Shaik, Y.; Sabatino, G.; Maccauro, G.; Varvara, G.; Murmura, G.; Saggini, A.; Rosati, M.; Conti, F.; Cianchetti, E.; Caraffa, A.; Antinolfi, P.; Pandolfi, F.; et al.
IL-36 is another family member of IL-1 and induces the production of proinflammatory cytokines and activates MAPK and NFκB pathways. IL-36 is a common mediator of innate and adaptive immune response and is inhibited by IL-36 receptor antagonist (RA). IL-36RA acts on IL-36 receptor ligand which exerts proinflammatory effect in vivo and in vitro . IL-38 binds to IL-36 receptor as does IL-36RA and has similar biological effects on immune cells. IL-38 is also a member of IL-1 cytokine and shares some characteristics of IL-1RA, binding the same IL-1 receptor type I. IL-38 plays a role in the pathogenesis of inflammatory diseases, exerting protective effect in some autoimmune diseases. Both IL-38 and IL-36RA have an anti-inflammatory biological effect, however in some cases have contrary effects.